The Optimization of Short-Term Hepatocyte Preservation Before Transplantation. Issue 7 (July 2017) - Fukuoka, Kengo; Inagaki, Akiko; Nakamura, Yasuhiro; Matsumura, Muneyuki; Yoshida, Satoru; Imura, Takehiro; Igarashi, Yasuhiro; Miyagi, Shigehito; Ohashi, Kazuo; Enosawa, Shin; Kamei, Takashi; Unno, Michiaki; et al.
Abstract : Background: No optimal methods for short-term hepatocyte preservation have been established. We have recently developed a prominent oxygen-permeable bag (Tohoku Device [TD]) for pancreatic islet culture and transplantation. In this study, we investigated whether TD is also effective for hepatocyte preservation and tried to optimize other conditions. Methods: Hepatocytes were preserved in the following conditions, and their outcomes were observed. First, the effectiveness of TD was investigated. Second, hepatocyte medium (HM) and organ preservation solutions with or without fetal bovine serum (FBS) were compared. Third, as supplementations, FBS and human serum albumin (HSA) were compared. Fourth, low, room and high temperature were compared. And finally, hepatocytes preserved in various conditions were transplanted into the subrenal capsule space of nonalbumin rats and engrafted areas were assessed. Results: The survival rate of hepatocytes preserved in TD tended to be higher and their viability and function were maintained significantly greater than those of non-TD group. Irrespective of FBS supplementation, the survival rate of HM group was significantly higher than those of organ preservation solution group while viabilities and plating efficiency were similar among them. Although survival rates of groups without FBS were extremely low, results of HSA supplemented group were not inferior to FBS supplemented group. Hepatocytes preserved at high temperature had the worst results. The engrafted area of TD group tended to be higher than those of other groups. Conclusions: TD is effective for short-term hepatocyte preservation. HSA is a useful substitute for FBS, and preserving in HM at low temperature is recommended.